AB1280 Predicting work disability, pension claim, absenteeism and presenteeism in ra patients. (12th June 2018) - Houssien, A.D.; Yates, M.; Norton, S.; Galloway, J.
Abstract : Background: Despite advances in treatments for Rheumatoid Arthritis (RA) a high prevalence of unemployment and work disability (WD) is reported; almost one third of affected patients leave the work force within two years of diagnosis. However, historic studies focused upon work disability as a dichotomous outcome, whereas more recent research has shifted the focus to work productivity, absenteeism and presenteeism. Objectives: We undertook a systematic review of observational studies to identify the known predictors of work productivity from work disability and identify the gap in between. Methods: A systematic search of Medline and Embase and PsychINFO since 2000 was undertaken using search terms: "Rheumatoid arthritis", "Disability", "Employment", "Work", "Occupation", "presenteeism", "absenteeism", "productivity" and "indirect cost". Original publications, all observational studies, reporting on predictors of work outcomes in RA were eligible. Clinical trials of drug therapies were excluded. All article titles were manually reviewed by 2 reviewers (AH and MY) and relevant abstracts was discussed and agreed, for which full text articles were sourced. Selected articles were assessed for quality using: QUality In Prognosis Studies (QUIPS) for observational studies. The heterogeneity in study designs meant meta-analysis was not appropriate. Therefore, To account for variation across studies in outcome measures used, an albatross plot was used to confirm predictors that were significantly associated with adverse work outcome. Results: In total 57 observational studies were included in the review, with data collectively on 83 686 patients. The studies were from 19 different countries, predominantly including developed countries. There was substantial heterogeneity across studies in terms of predictors evaluated as well as how work productivity was estimated. More contemporary studies were more likely to capture information on mental health as a predictor. Consistent significant predictors of work outcome could be divided into 1 demographic factors: older age, obesity, lower educational level, job type, commuting difficulty; 2 disease factors: higher disease activity, longer disease duration, joint erosions, longer morning stiffness, higher disability; 3 comorbidity: concomitant mental health disorder, fibromyalgia or cardiovascular disease. Conclusions: The review highlights the lack of consistency in the use of validated work outcome measures in research. The key determinant of work disability extends beyond disease severity measures, and in particular mental health is emerging as a pivotal component of health that predicts ability to remain within the work force. Disclosure of Interest: None declared